STYLISTIC ANALYSIS OF POEMS IN UZBEK AND ENGLISH LANGUAGES (Scientific journal of the Fergana State University, 2023)
The aim of this article is to describe the types of stylistic devices and their role in enhancing the impact of poetry. Examples of the use of stylistic devices in poetic texts are given. Stylistically analyzed poems in English and Uzbek languages.It is concluded that on the basis of stylistic analysis it is possible to explore the language of a work of art, find the final figurative information in it and at the same time not reduce the analysis to a set of disparate micro-images, not deprive the poem of its poetic charm and integrity.